2015
DOI: 10.1186/s12916-015-0529-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral brain-derived neurotrophic factor (BDNF) as a biomarker in bipolar disorder: a meta-analysis of 52 studies

Abstract: BackgroundThe neurotrophic hypothesis postulates that mood disorders such as bipolar disorder (BD) are associated with a lower expression of brain-derived neurotrophic factor (BDNF). However, its role in peripheral blood as a biomarker of disease activity and of stage for BD, transcending pathophysiology, is still disputed. In the last few years an increasing number of clinical studies assessing BDNF in serum and plasma have been published. Therefore, it is now possible to analyse the association between BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
147
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(161 citation statements)
references
References 97 publications
10
147
4
Order By: Relevance
“…Finally, cascades associated with the activation of the aforementioned pathways appear to lead to excitotoxic neural damage, a reduced expression of brain derived neurotrophic factor (BDNF) and consequently to a disruption of mechanisms subserving neural plasticity 53,54 . In addition, oxidative stress may reduce the activity of 5,6,7,8-tetrahydrobiopterin (BH4), which is a co-factor for several aromatic amino acid monooxygenases and is rate-limiting for the biosynthesis of the neurotransmitter serotonin and the catecholamines dopamine, epinephrine and norepinephrine 55 .…”
Section: Inflammatory Aberrations Associated With Depressionmentioning
confidence: 99%
“…Finally, cascades associated with the activation of the aforementioned pathways appear to lead to excitotoxic neural damage, a reduced expression of brain derived neurotrophic factor (BDNF) and consequently to a disruption of mechanisms subserving neural plasticity 53,54 . In addition, oxidative stress may reduce the activity of 5,6,7,8-tetrahydrobiopterin (BH4), which is a co-factor for several aromatic amino acid monooxygenases and is rate-limiting for the biosynthesis of the neurotransmitter serotonin and the catecholamines dopamine, epinephrine and norepinephrine 55 .…”
Section: Inflammatory Aberrations Associated With Depressionmentioning
confidence: 99%
“…Plasma and partially serum, BDNF levels were modified in several diseases and conditions such as: fibromyalgia [increased (196)], hemodialysis [increased, especially in diabetic patients (197)], metabolic syndrome and T2DM [increased (198)], bipolar disorder [decreased (199)], as well as with mood, cognition and motor function (200), alcohol consumption [decreased (201)], antidepressant treatments [increased (202)]. …”
Section: Pre-analytical Factorsmentioning
confidence: 99%
“…Several studies have adopted the BDNF as a molecular candidate for developing bipolar disorder [6,10]. Recent studies had demonstrated that BDNF levels are lower in patients during active phases than BDNF levels in healthy controls [10][11][12][13][14]. Changes in serum BDNF levels in different phases and in following pharmacological interventions for acute affective phase in patients with bipolar disorders were addressed in several studies, but the results are still inconclusive [8,13,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in serum BDNF levels in different phases and in following pharmacological interventions for acute affective phase in patients with bipolar disorders were addressed in several studies, but the results are still inconclusive [8,13,[15][16][17]. The serum BDNF protein level is reported to be a useful adjunctive tool for accurately diagnosing depressive bipolar disorder [18] and a marker for treatment response in bipolar disorder [11,14,19]. Bipolar disorder confers the higher risk of suicide and violence among major psychiatric disorders [20,21].…”
Section: Discussionmentioning
confidence: 99%